Pengaruh sukrosa terhadap mutu kurma analog belimbing wuluh - Desi Arisanti (Program Studi Teknologi Hasil Pertanian, Politeknik Gorontalo, 2017)
Wuluh starfruit (Averrhoa bilimbi L) is widely spread in Indonesia as a home garden that has not been cultivated. In addition, the sour taste and high water content in the fruit causes the fruit is rarely consumed directly and the relative shelf life is relatively short. One of the ways of fruit development is to be a wuluh starfruit (analog kurma). This study aimed to determine the level of palm fruits analogous to the combination of wuluh starfruit and sucrose, to know the content of some chemical properties of analog dates. The method used in this final project was a method of testing of organoleptic test, water content test, sugar content test, ash content test, and vitamin C content test. The results showed the results of organoleptic test had a favorite level that resulted from three treatment dates with analog combination The composition of wuluh starfruit and sucrose as a whole was on the scale of 3,25 – 3,90 or in the usual level until rather like. The analog dates preferred by panelists were the A3 treatment and based on the analysis of the date palm analogue with the combination of wuluh starfruit and sucrose composition was very significant effect on water content and